MOTHER’S PERCEPTIONS BASED ON THE HEALTH BELIEF MODEL ABOUT EXCLUSIVE BREASTFEEDING IN PREVENTING STUNTING AT KAMPUNG BARU PUBLIC HEALTH CENTER, MEDAN MAIMUN DISTRICT, MEDAN CITY, NORTH SUMATRA PROVINCE, 2025 - Sibarani, Lisa Erawati; Pangaribuan, Ingka; Srilina Br Pinem; Adi Raja Lubis; Dwi Hasanah; Sari N Manalu; Feby Anggani Situmorang (Mitra Husada Health Internasional Conference (MIHHICo), 2025)
Sustainable Development Goal (SDG) number two aims to create a healthy and productive society free from hunger. According to SDG data, the stunting rate among children under five decreased from 24.4% in 2021 to 21.6% in 2022. However, disparities remain across provinces, and national targets have not yet been achieved. Stunting is characterized by a Z-score less than -2 SD (moderate) and less than -3 SD (severe). One of the main obstacles to achieving this goal is the prevalence of malnutrition among children under five, which is a major factor contributing to stunting (Bappenas, 2023). This study aims to explore mothers’ perceptions using the Health Belief Model (HBM) regarding exclusive breastfeeding in preventing stunting at the Kampung Baru Health Center in 2025. The research method is analytical, using a cross-sectional design with a Chi-Square test to analyze the influence between variables. The population consists of all mothers with toddlers, with a total of 149 visits recorded in the past year. A sample of 60 mothers was selected. Primary data were collected using questionnaires, and secondary data were obtained through interviews. The results showed that most respondents were aged 31–40 years (66.7%), had a high school education (66.7%), and were housewives (91.7%). There was a statistically significant relationship between perceived susceptibility (p=0.009), perceived severity (p=0.024), and perceived benefits (p=0.013) with the practice of exclusive breastfeeding in preventing stunting. In contrast, perceived barriers did not show a significant influence (p=0.709). Conclusion: There is a significant relationship between mothers’ perceptions of susceptibility, severity, and benefits and the practice of exclusive breastfeeding in preventing stunting, while perceived barriers had no significant impact. Educational interventions should focus on enhancing mothers’ positive perceptions of the importance of exclusive breastfeeding.